Development of a Natural Science Module with a STEM Approach on Liquid Substance Pressure for Class VIII SMP/MTs - Frisci Windavi Riri Agitha; Rafiatul Hasanah (Indonesian Journal of Mathematics and Natural Science Education, 2022)
This study aims to describe the validity and responses of students to the natural science module with the STEM approach in the sub-material of liquid pressure. The research model uses a 4D model developed by Thiagarajan (define, design, develop and disseminate) but this study only reached the development stage. The development of the science module was validated by material expert validators, media experts, and user experts (teachers) with an average percentage of 93.63% with a very valid category. The results of the small-scale student response test of 86.1% to determine the readability of the media, then the large-scale test obtained 86.74 %, thus this science module is categorized as very interesting. This module contains sub-materials of fluid pressure consisting of hydrostatic pressure, Archimedes' law, and Pascal's law. In each material, there are illustrations to support the depth of the materials.